NAL1 allele from a rice landrace greatly increases yield in modern indica cultivars - Fujita, Daisuke; Trijatmiko, Kurniawan Rudi; Tagle, Analiza Grubanzo; Sapasap, Maria Veronica; Koide, Yohei; Sasaki, Kazuhiro; Tsakirpaloglou, Nikolaos; Gannaban, Ritchel Bueno; Nishimura, Takeshi; Yanagihara, Seiji; Fukuta, Yoshimichi; Koshiba, Tomokazu; et al. (National Academy of Sciences, 2013)
This work reports discovery of a unique gene important for rice agriculture. A significant yield enhancement in rice modern cultivar was achieved by identification of a gene, SPIKELET NUMBER ( SPIKE ) in Indonesian rice landrace. The SPIKE increased grain yield of an indica cultivar IR64, which is widely grown in the tropics, over four seasons at the field level and improved plant architecture without changing grain quality or growth period, which are important for regional adaptability. These results indicate finding of SPIKE will be extremely valuable for contributing to increase grain production of indica rice cultivars.